STRATEGIES TO IMPROVE THE SUSTAINABILITY IN PROMOTING TRANSPARENCY, ACCOUNTABILITY AND ANTI-CORRUPTION: AN IMAGINARY DIALOGUE - Sukoharsono, Eko Ganis (Accounting Department,, 2018)
The paper is an imaginary dialogue. The dialogue is between two professionals: SDGist and Auditor. To bring up their imagination, postmodernism is used to explore the dialogue. Both are trying to discuss the current issues on SDGs. The objective of the paper is to explicate strategies to improve SDGs in promoting transparency, accountability and anti-corruption, which is in particular to promote peaceful and inclusive societies for sustainable development, provide access to justice for all and build effective, accountable and inclusive institutions at all levels, especially on the Goal 16.4 to 16.6.The result of the dialogue, there are 9 strategies to improve the SDGs in promoting transparency, accountability and anti-corruption. They are the ICSP on SDGs Implementation: Socializing the Sustainability Reporting, implementing of e-government, promoting more investment, fitting policies nationally and internationally relevant to the goal 16.4 to 16.6, supporting inclusive growth and well being, ensuring the 5Ps’ sustainability, promoting partnerships, strengthening data availability and capacity, and facilitating follow up and review.